Re-analysis of tropospheric sulfate aerosol and ozone for the period 1980–2005 using the aerosol-chemistry-climate model ECHAM5-HAMMOZ - Pozzoli, L.; Janssens-Maenhout, G.; Diehl, T.; Bey, I.; Schultz, M. G.; Feichter, J.; Vignati, E.; Dentener, F. (Atmospheric chemistry and physics, 2011)
Understanding historical trends of trace gas and aerosol distributions in the troposphere is essential to evaluate the efficiency of existing strategies to reduce air pollution and to design more efficient future air quality and climate policies. We performed coupled photochemistry and aerosol microphysics simulations for the period 1980–2005 using the aerosol-chemistry-climate model ECHAM5-HAMMOZ, to assess our understanding of long-term changes and inter-annual variability of the chemical composition of the troposphere, and in particular of ozone and sulfate concentrations, for which long-term surface observations are available. In order to separate the impact of the anthropogenic emissions and natural variability on atmospheric chemistry, we compare two model experiments, driven by the same ECMWF re-analysis data, but with varying and constant anthropogenic emissions, respectively. Our model analysis indicates an increase of ca. 1 ppbv (0.055 ± 0.002 ppbv yr−1) in global average surface O3 concentrations due to anthropogenic emissions, but this trend is largely masked by the larger O3 anomalies due to the variability of meteorology and natural emissions. The changes in meteorology (not including stratospheric variations) and natural emissions account for the 75 % of the total variability of global average surface O3 concentrations. Regionally, annual mean surface O3 concentrations increased by 1.3 and 1.6 ppbv over Europe and North America, respectively, despite the large anthropogenic emission reductions between 1980 and 2005. A comparison of winter and summer O3 trends with measurements shows a qualitative agreement, except in North America, where our model erroneously computed a positive trend. Simulated O3 increases of more than 4 ppbv in East Asia and 5 ppbv in South Asia can not be corroborated with long-term observations. Global average sulfate surface concentrations are largely controlled by anthropogenic emissions. Globally natural emissions are an important driver determining AOD variations. Regionally, AOD decreased by 28 % over Europe, while it increased by 19 % and 26 % in East and South Asia. The global radiative perturbation calculated in our model for the period 1980–2005 was rather small (0.05 W m−2 for O3 and 0.02 W m−2 for total aerosol direct effect), but larger perturbations ranging from −0.54 to 1.26 W m−2 are estimated in those regions where anthropogenic emissions largely varied.